Clinical implications and risk factors for QRS width progression in heart failure patients. (3rd October 2022) - Berger, M; Kumowski, N; Straw, S; Verket, M; Marx, N; Witte, K K; Schuett, K
Abstract: Background: QRS complex prolongation is an established prognostic marker in patients with heart failure, (HF) and identifies patients for whom standard treatment includes cardiac resynchronization therapy (CRT). In contrast, the role of QRS width progression over time on clinical status and whether it can be predicted has been incompletely explored. Purpose: To provide pilot data that could help to identify features associated with QRS progression and deteriorating clinical status. Methods: The present retrospective analysis relates to 100 consecutive attendees to our HF clinic between April and August 2021. Each patient with a least one past visit including an ECG was included and a maximum of 4 past visits were assessed per patient. Results: In total 240 datasets were generated from at least two consecutive visits and included clinical status, electrocardiographic (ECG), laboratory and echocardiographic data. Mean age and left ventricular ejection fraction were 58±13 years and 36±10%. The mean time between visits was 227 days. Datasets were stratified into tertiles based on change in QRS duration (mm/month). These were labelled as "QRS width regression" (>−0.34 ms/month), "QRS stability" (−0.33 to 0.49 ms/month and "QRS width progression" (>0.50 ms/month). The incidence of the combined endpoint of worsening symptomatic HF (deterioration in NYHA class by at least one grade) and HF hospitalisation was significantly higher in the QRS progression group compared with the stable group (Log Rank test: progression v stability p=0.013). In addition, patients with QRS progression had a higher baseline plasma NT-pro-BNP levels (p=0.008) and higher baseline heart rate (p=0.007). To explore whether patients at higher risk of QRS progression could be identified at baseline, we built a prediction model based upon baseline NTproBNP levels and baseline heart rate. We determined that an NT-pro-BNP >837 pg/ml and a heart rate >83/bpm were reliable thresholds for greater risk of QRS progression (Figure 1A & B). Both of these variables were independent of guideline-directed medical HF therapy (including beta-antagonist use and dose). An interaction analysis revealed that combining these two risk factors was associated with a 14-fold increased risk of QRS progression compared with neither or either alone, suggesting synergism between these variables (HR: 14.2 [95% 6.9–53.6]; p<0.0001, p for interaction=0.016). Conclusion: In the current pilot study, we demonstrate that QRS progression is associated with future risk of clinical deterioration of HF. In addition, we show that higher baseline NTproBNP plasma levels combined with higher baseline heart rate indicate a group at markedly increased risk of progression of QRS width, independently of HF therapy. These parameters might therefore identify people potentially benefitting from intensified follow up, optimisation of GDMT and could also help coordinate the application of a more personalised approach to device therapy Funding Acknowledgement: Type of funding sources: None.